2008
DOI: 10.1042/bj20080714
|View full text |Cite
|
Sign up to set email alerts
|

A ternary complex of hydroxycinnamoyl-CoA hydratase–lyase (HCHL) with acetyl-CoA and vanillin gives insights into substrate specificity and mechanism

Abstract: HCHL (hydroxycinnamoyl-CoA hydratase-lyase) catalyses the biotransformation of feruloyl-CoA to acetyl-CoA and the important flavour-fragrance compound vanillin (4-hydroxy-3-methoxybenzaldehyde) and is exploited in whole-cell systems for the bioconversion of ferulic acid into natural equivalent vanillin. The reaction catalysed by HCHL has been thought to proceed by a two-step process involving first the hydration of the double bond of feruloyl-CoA and then the cleavage of the resultant beta-hydroxy thioester by… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
50
0

Year Published

2009
2009
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 42 publications
(53 citation statements)
references
References 39 publications
3
50
0
Order By: Relevance
“…A similar strategy is employed by hydroxycinnamoyl-CoA hydratase–lyase (HCHL), another crotonase superfamily member that uses two Tyr residues as a molecular “pincer” to recognize the substrate, initiate deprotonation and exert strain on the substrate. The two Tyr residues in HCHL are located on analogous loops to those found in MenB (Figure 4), one of which is also only observed when the analogous A-loop in HCHL becomes ordered (48). …”
Section: Resultsmentioning
confidence: 85%
See 3 more Smart Citations
“…A similar strategy is employed by hydroxycinnamoyl-CoA hydratase–lyase (HCHL), another crotonase superfamily member that uses two Tyr residues as a molecular “pincer” to recognize the substrate, initiate deprotonation and exert strain on the substrate. The two Tyr residues in HCHL are located on analogous loops to those found in MenB (Figure 4), one of which is also only observed when the analogous A-loop in HCHL becomes ordered (48). …”
Section: Resultsmentioning
confidence: 85%
“…Throughout the MenB family, this residue is either an Asp or a Gly (Figure 4). Although G156 or the water molecule does not appear to play a major role during α-deprotonation or stabilization of the two oxyanion intermediates based on our ecMenB structure, a glutamate or water in a similar position has been proposed to perform acid/base catalysis in a number of crotonase superfamily members including ECH (62), dienoyl-CoA isomerase (63), ECI, (64), HCHL, (48) and DpgC (39). The bicarbonate dependence in the MenB activities of E. coli , S. aureus and B. subtilis and the presence of bicarbonate in the crystal structure of stMenB also has led to a proposal that D185 is used for α-deprotonation in mtMenB and that a bicarbonate cofactor performs the same function when the Asp is replaced by a Gly as in ecMenB, saMenB and bsMenB (21).…”
Section: Resultsmentioning
confidence: 89%
See 2 more Smart Citations
“…A labelling study using deuterated ferulic acid and Pycnoporus cinnabarinus showed that, by analogy to fatty acid degradation, the mechanism comprised the hydration of the double bond of feruloyl-CoA and then the cleavage of the resultant b-hydroxy thioester by a retro-aldol reaction (Krings et al 2001). Recently, the crystal structure of a substrate bound hydroxycinnamoyl-CoA hydrataselyase was reported (Bennett et al 2008). Only a few flavour formation pathways have received this high degree of attention.…”
Section: Cell Based Processesmentioning
confidence: 98%